SYMBOLIC INTERACTION OF THE MAIN CHARACTER IN THE NOVEL LAUT BERCERITA BY LEILA S. CHUDORI - Jambak, Melinda Raswari; Hakim, Arief Rahman; Roziki, Khafid (Annual International Conferences on Language, Literature, and Media, 2023)
The emergence of dissent against the new era regime led to the unaccounted absence of thirteen student activists from Yogyakarta. The event was immortalized by Leila S. Chudori through her remarkable novel entitled "Laut Bercerita." The objective of this study is to examine the portrayal of the mind, self, and society in the characters of Biru Laut and Asmara Jati in the novel Laut Bercerita by Leila S. Chudori. Specifically, this research aims to (1) provide a comprehensive analysis of the concept of mind as depicted in these characters, (2) elucidate the concept of self as portrayed in Biru Laut and Asmara Jati, and (3) explore the representation of society in the context of these characters. The focus of this study is the literary work entitled "Laut Bercerita" authored by Leila S. Chudori, along with several scholarly sources like books and journals that provide relevant insights and perspectives for the research. The research methodology employed in this study is descriptive qualitative in nature. The data were acquired through the utilization of reading and note-taking methodologies. The activities involved in the analysis encompass three main steps: data reduction, data presentation, and conclusion drawing and verification. The findings of this research revealed the presence of two distinct conceptual frameworks related to the mind, namely "Seyegan House" and "Asmara Jati's concerns." The notion of self is explored in the literary works "Kidnapping Biru Laut" and "Asmara Jati’s Decision." The notion of society is explored in the works "Blangguan Corn Planting Action 1993" and "Kamisan Action 2007."